PENENTUAN TINGKAT KEKERINGAN LAHAN BERBASIS ANALISA CITRA ASTER DAN SISTEM INFORMASI GEOGRAFIS ( KASUS DI SEBAGIAN WILAYAH KABUPATEN GUNUNG KIDUL PROVINSI DAERAH ISTIMEWA YOGYAKARTA ) - , Alfian Pujian Hadi ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Dryness of farm knocking over an area to generate big impact to agricultural land productivity. The happening of this dryness because of water deficit as result of lack of falling rain, high water infiltration velocity and crop type which unmatched to water availability. Minimization of Impact to happened as result of dryness of farm hence need to be done anticipation given the deficit and surflus farm water through rainfall data and ability of soil land ground arrest detains water (water holding capasity). For the purpose is required dryness analysis of farm with using remote sensing image and farm water balance as initial knowledge utilized planning of anticipation of dryness of farm so that amount of water required for crop can fufilled every when. This research done in this part of gunung kidul regency, purpose of this research is : (1) Studies accuration various channels TIR image Aster to get information as of land surface temperature (2) Studies of dryness through index TVDI (Temperature Vegetation Dryness Indeks) extract from surface temperature (Land Surface Temperature) and index NDVI. ( 3) Studies level of dryness of farm by using method Thornthwaite-Mather, (4) Studies cropping pattern appropriate is applied in research region. Result of research indicates that channel 13 images Aster had highest accuration if it is compared to channel 10,11,12, and 14 images Aster because having smallest difference with field surface temperature. Based on analysis RMS difference is obtained by value 1,140. Wide as of dryness based on index TVDI at all land use with level of high dryness, knocking over each low and medium area with a width of 2922,8 Ha (4,6%), 20286,16 Ha (32,11%) and 39962,72 Ha (63,26%). From wide total 2922,8 Ha farm knocked over by dryness with level of high dryness (less water) with a width of 2069,47 Ha is wet ricefield dependant to rain. Analysis the relation of index TVDI with soil moisture rate shows rapport that is overweening not equal to 53,7% Level of dryness of farm with water balance analysis Thornthwaite-Mather shows dryness index (aridity index) stays in level of medium dryness and weight. Dryness is happened at land unit affecting station of rain Giriwungu (Panggang), Kedung Keris, Gedangan and some of Playen. Dryness of weight happened at land unit affecting station of rain Wonosari, Tepus and some of Playen. Cropping pattern based on agroklimat Oldeman is grouped into cropping pattern Padi Gogo (Palawija)-Palawija-Bero, Padi Sawah-Palawija-Bero, Palawija-Palawija-Bero. Cropping Pattern (Palawija)-Palawija- Bero is applied in wet ricefield dependant to rain and non irigated dry field at land unit affecting station of rain Tepus and Panggang with planting season 1 happened Oktober- January and planting season 2 happened in Februari-May, cropping pattern Padi Sawah- Palawija-Bero is applied in rice field and wet ricefield dependant to rain at land unit affecting station of rain Wanagama ( Playen), Kedung Keris and Gedangan with planting season 1 happened in November-February and planting season 2 happened in Maret-Juni while cropping pattern Palawija-Palawija-Bero is applied in blend garden at land unit affecting station of rain Kedung Keris, Gedangan, Playen, and Wonosari for wet ricefield dependant to rain where planting season 1 happened in November-February and planting season 2 happened in March-June.